Regional pattern of microgliosis in sporadic Creutzfeldt‐Jakob disease in relation to phenotypic variants and disease progression. (26th February 2018) - Franceschini, A.; Strammiello, R.; Capellari, S.; Giese, A.; Parchi, P.
Abstract : Aims: The aim of this study was to describe the regional profiles of microglial activation in sporadic Creutzfeldt‐Jakob disease (sCJD) subtypes and analyse the influence of prion strain, disease duration and codon 129 genotype. Methods: We studied the amount/severity and distribution of activated microglia, protease‐resistant prion protein (PrP Sc ) spongiform change, and astrogliosis in eight regions of 57 brains, representative of the entire spectrum of sCJD subtypes. Results: In each individual subtype, the regional extent and distribution of microgliosis significantly correlated with PrP S c deposition and spongiform change, leading to subtype‐specific 'lesion profiles'. However, large differences in the ratio between PrP Sc load or the score of spongiform change and microglial activation were seen among disease subtypes. Most significantly, atypical sCJD subtypes such as VV1 and MM2T showed a degree of microglial activation comparable to other disease variants despite the relatively low PrP S c deposition and the less severe spongiform change. Moreover, the mean microglial total load was significantly higher in subtype MM1 than in MM2C, whereas the opposite was true for the PrP Sc and spongiform change total loads. Finally, some sCJD subtypes showed distinctive regional cerebellar profiles of microgliosis characterized by a high granular/molecular layer ratio (MV2K) and/or a predominant involvement of white matter (MVK and MM2T). Conclusions: Microglial activation is an early event in sCJD pathogenesis and is strongly influenced by prion strain, PRNP codon 129 genotype and disease duration. Microglial lesion profiling, by highlighting strain‐specific properties of prions, contributes to prion strain characterization and classification of human prion diseases, and represents a valid support to molecular and histopathologic typing.